Coal-fired power plant airborne particles impact towards human health - Mohd. Din, Shamzani Affendy; Nik Yahya, Nik Nurul Hidayah; Hanapi, Norsyamimi; Abdullah, Alias (Universiti Teknologi Malaysia, 2015)
The explosion of global warming and climate change occurs parallel to the raise rise of earth development. These phenomena happen due to the deterioration of atmospheric environment rooted from human activity. Ranges of air pollutants had been discovered. However, this research focuses on airborne particles in particular that comes from the emissions of coal. Recently, Malaysia electricity demand is raising and leads to the diversification of its sources towards the non-renewable energy. Manjung coal-fired power plant emission had been recognised as one of the potential anthropogenic sources of airborne particles. 8-hours airborne particles sampling had been done at Manjung Power Plant in March and July 2011 with 7-hole sampler at 2 L/min air flow and cyclone sampler at 2.2 L/min airflow. This research found that total inhalable dust exceeds 96.78 %; PM10 standard of 0.15mg/m3.This study also found that the percentage ratio of respirable towards total inhalable dust is 33.49%. This study also found that, as the temperature increases, the airborne particles concentration also increases. It is believed that the smaller offers particulate higher degree of illness. Thus, it is believed, the airborne particles dissemination from its sources is affected by the climate of an environment. Whichcan be deposited into deeper part of lung and provide adverse health impact towards the public or residence of surrounding coal-fired power plant neighbourhood area, generally and coal workers, specifically.